Non clostric:lial gaseous infection - Torterolo Prado, Edgardo; Morelli Brum, Raúl; Silva, Celso; Viñuelas, Enrique; de Vecchi, Jorge (Cirugía del Uruguay, 1977)
The authors analyze 15 cases of infections of soft parts caused by gas-producing germs. Local predisposing factors are of importance due to the fact that, in reducing oxidation-reduction potential, they favour development and spreding of infection. Direct gram study is of importance in identifying the germ, the culture of which is difficult. Clinics is similar to that of clostridial cellulitis. Regardless of bacteriological findings. the main treatment consists in surgery with broad incisions and tissue abscission.